Pengaruh Penilaian Kinerja dan Pelatihan terhadap Kinerja Karyawan Melalui Kemampuan Kerja sebagai Variabel Intervening pada PT. Hakaaston Sungai Lansek - Bella Risky; Selvi Yona Sari; Nila Pratiwi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
PT. Hakaaston Sungai Lansek is a company engaged in manufacturing and infrastructure construction. This study aims to analyze the effect of performance appraisal and training on employee performance through work ability as an intervening variable at PT. Hakaaston Sungai Lansek. The population and sample consist of all employees of the company. Data were collected through questionnaires and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with SmartPLS 3.0. The results of the study indicate that performance appraisal does not have a positive and significant effect on work ability, while training has a positive and significant effect on work ability. Furthermore, performance appraisal has a positive and significant effect on employee performance, whereas training does not have a positive and significant effect on employee performance. Work ability is proven to have a significant effect on employee performance. The results of the indirect effect analysis show that work ability is not able to mediate the effect of performance appraisal on employee performance; however, it is able to mediate the effect of training on employee performance. Thus, work ability plays an important role in improving employee performance, particularly through the effective implementation of training.